Human fucci pancreatic Beta cell lines: new tools to study Beta cell cycle and terminal differentiation. - Géraldine Carlier (Public Library of Science (PLoS), 2014)
Regulation of cell cycle in beta cells is poorly understood, especially in humans. We exploited here the recently described human pancreatic beta cell line EndoC-βH2 to set up experimental systems for cell cycle studies. We derived 2 populations from EndoC-βH2 cells that stably harbor the 2 genes encoding the Fucci fluorescent indicators of cell cycle, either from two vectors, or from a unique bicistronic vector. In proliferating non-synchronized cells, the 2 Fucci indicators revealed cells in the expected phases of cell cycle, with orange and green cells being in G1 and S/G2/M cells, respectively, and allowed the sorting of cells in different substeps of G1. The Fucci indicators also faithfully red out alterations in human beta cell proliferative activity since a mitogen-rich medium decreased the proportion of orange cells and inflated the green population, while reciprocal changes were observed when cells were induced to cease proliferation and increased expression of some beta cell genes. In the last situation, acquisition of a more differentiated beta cell phenotype correlates with an increased intensity in orange fluorescence. Hence Fucci beta cell lines provide new tools to address important questions regarding human beta cell cycle and differentiation.